Assessment of Eyelid Pressure Using a Novel Pressure Measurement Device in Patients With Moderate-to-Severe Dry Eye Disease - Wang, Jingyi; Bao, Jiayu; Song, Wenxiu; Li, Siyuan; Hao, Yiran; Tian, Lei; Jie, Ying (Frontiers in Medicine, 2022)
Objective To assess a novel eyelid pressure measurement device and study the relationship between eyelid pressure and ocular surface parameters of moderate-to-severe dry eye disease (DED). Methods The present study included 70 eyes of 35 moderate-to-severe DED patients. All subjects were subjected to the following examinations for DED assessment: Ocular Surface Disease Index (OSDI) questionnaire, tear meniscus height (TMH), lipid layer thickness (LLT), number of partial blink (PB), total blink (TB) and partial blink rate (PBR), fluorescein tear breakup time (FBUT), corneal fluorescein staining (CFS), lid margin abnormality, meibum expression assessment (meibum score), meibomian gland dropout (MGd) and Schirmer I test. Pressure of the upper eyelid was measured thrice with the novel pressure measurement device. Repeatability of the device was evaluated by intraclass correlation coefficient (ICC). Safety of the device was evaluated by observing ocular adverse reactions of each subject prior to measurement, at day 1 and day 7 following measurement. Correlations between eyelid pressure and ocular surface parameters of moderate-to-severe DED were analyzed by using Pearson correlation coefficient and Kendall's tau-b correlation coefficient. Results ICC of the measurement results in our study was 0.86. There was no abnormality presenting in all subjects recorded prior to measurement, 1 and 7 days following measurement. The eyelid pressure was significantly correlated with PBR (r = 0.286, P = 0.016), FBUT (r = −0.331, P = 0.005), CFS (r = 0.528, P = 0.000), lid margin abnormality (r = 0.408, P = 0.011) and MGd (r = 0.226, P = 0.016) in moderate-to-severe DED patients, but not significantly correlated with OSDI score (r = 0.016, P = 0.912), TMH (r = −0.002, P = 0.988), meibum score (r = −0.196, P = 0.317), LLT (r = 0.114, P = 0.346), PB (r = 0.116, P = 0.338), TB (r = 0.074, P = 0.544), meibum score (r = −0.196, P = 0.317) and Schirmer I test (r = 0.028, P = 0.821). Conclusion The novel pressure measurement device exhibited good repeatability and safety in measuring eyelid pressure. Significant correlations were noted between the eyelid pressure and PBR, FBUT, CFS, lid margin abnormality and MGd in moderate-to-severe DED. The measurement of eyelid pressure combined with ocular surface parameters may be valuable for the assessment of DED.